Onicomicoses por fungos filamentosos e tratamento pela utilização de laser (1340nm) - Espírito Santo, Graciela Araújo do (2016)
The onychomycosis are fungal infections of nail plates with worldwide prevalence of between 2 to 8% of the population and 24% in the elderly low perfusion of the extremities. The most common etiologic agents are represented by dermatophyte fungi, yeasts and fungi not dermatophytes. Clinically, onychomycosis are manifested by onycholysis, hyperkeratosis, change in color and decrease in the nail plate growth time. They are predominantly treated with topical antifungal agents (amorolfine and ciclopirox olamine) in enamels, and oral (fluconazole, itraconazole and terbinafine). In 2010 the FDA (Food and Drug Administration) approved several laser equipment for the treatment of onychomycosis. This study aimed to evaluate the frequency and use of laser 1340nm as monotherapy in clinical conditions compatible with onychomycosis confirmed by mycological examination. Therefore, we selected 30 patients suffering from onychomycosis in toenails infected by fungi from the group of dermatophyte and non-dermatophyte fungi. They excluded patients who were in effect of other treatments for onychomycosis in the period before three months, pregnant women or children under 15 years. After the diagnosis, the patients were sent to collect samples (subungueal deposit and nail plate fragments) to perform mycological examination. After confirmation of fungal etiology, patients underwent three laser sessions, according interval of 3 weeks and re-evaluated after 3 months of the last session. mycological examinations to evaluate healing of control after the last session were held. Among the dermatophytes, T. rubrum was the most isolated fungus, followed by T. mentagrophytes. Considering filamentous fungi Fusarium spp not dermatophytic was the most frequent found results showed limited efficacy of this treatment modality, demonstrating that there is as yet choose only to use only the laser treatment in the case of onychomycosis.